Determination of thermal fields and adhesion temperature conditions in the model "liquid - alloy droplet - substrate" - Elena Kolesnikova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the discussed issue is caused by the need to advance thermal spray technology and the methods for determining the process best performance. The main aim of the study is to determine thermal fields and adhesion temperature conditions in the model «liquid-alloy droplet - substrate». The methods used in the study: the mathematical modeling for thermal fields and adhesion temperature conditions in the model «liquid - alloy droplet - substrate»; experimental validation of the results calculated with the proposed model. The results. The paper introduces the method for determining thermal fields in the model «liquid-alloy droplet - substrate» based on equalization of temperatures of fixed identical small size neighboring cubic volumes. The method is based on the concept that non-steady process of thermal heating approaches to steady-state process as time and dimensional gaps are reduced. The provided method is free from using differential equations. The calculation of non-steady thermal field is based on thermal transmission equation (algebraic equations). Adhesion temperature conditions for a droplet impacting on a solid surface are obtained. The thermal condition of adhesion is based on substrate melting. Partial adhesion corresponds to melting of the part of substrate surface, total adhesion corresponds to melting of the whole substrate surface. The proposed thermal adhesion condition is valid in case of lack of intermetallic compounds formation between spat and substrate materials. The calculated results are in accordance with the experimental data.